2009
DOI: 10.3928/08910162-20090201-02
|View full text |Cite
|
Sign up to set email alerts
|

Managers' Perceptions of the Current and Future Role of Occupational Health Nurses in Australia

Abstract: Occupational health nurses face competition from other professionals in the field of occupational health and safety. This study investigated managers' perceptions of Australian occupational health nurses' roles. Managers were asked to rate the importance of occupational health nurses' activities and the time they believe occupational health nurses do or should dedicate to each activity now and in the future. The questionnaire included 22 activity statements gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Mellor and St John (2007) revealed that the specific task of enhancing the health of workers and their families was ranked by Australian occupational health nurses as the second least important activity they performed currently or in the future. Mellor and St John (2009) reported that managers believed that little attention should be paid to occupational health nurses providing care to families. The work safety of fathers can therefore be viewed as a "blind spot" in occupational health and safety because fatherhood is not recognized as a workplace safety issue.…”
Section: Discussionmentioning
confidence: 99%
“…Mellor and St John (2007) revealed that the specific task of enhancing the health of workers and their families was ranked by Australian occupational health nurses as the second least important activity they performed currently or in the future. Mellor and St John (2009) reported that managers believed that little attention should be paid to occupational health nurses providing care to families. The work safety of fathers can therefore be viewed as a "blind spot" in occupational health and safety because fatherhood is not recognized as a workplace safety issue.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO (2005) reports on the risk factors of obesity, diabetes, physical inactivity, smoking, high cholesterol and recommended workplaces address these social concerns. Although the burden of disease varies throughout the world, articles from the USA (Chickotas & Olszewkski, 2007;Marinescu, 2007) and Australia (Mellor & St John, 2009) identify OHNs have a role in addressing these concerns. The ageing working population has health issues such as musculoskeletal problems, chronic conditions and increased stress.…”
Section: Ohns Address Lifestyle Diseasesmentioning
confidence: 99%
“…Businesses expect OHNs will have the skills and knowledge to provide a high quality OH service to protect and promote the health of the working population (WHO, 2012). Of the literature retrieved two research papers explored the perception of business management on the OHN's role (Mellor & St John, 2009;Nelson, 2001) and the activities they would like them to undertake. The data revealed businesses expected the OHN to implement health promotion programmes, promote the rehabilitation of injured workers, and management and research, to support and maintain the health of their workforce.…”
Section: Ohns Must Provide a Quality Service To Businessesmentioning
confidence: 99%
See 1 more Smart Citation